Types and Sources of Antioxidants that Role in Determining Fertility Level - Sri Winarni; Ari Udijono; Atik Mawarni; Dharminto Dharminto; Oktavia Beni Kujariningrum; Waviq Azizah (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Lifestyle and exposure of free radicals affect in a person’s fertility. ROS (Reactive Oxygen Species) in excess can caused oxidative stress and DNA damage (deoxyribonucleic acid). Adequate intake of antioxidants is needed to maintain ROS level. This review’s aim is determine the types and sources of antioxidants that play a role in determining a person’s fertility level. This research is a narrative review using a literature review method by collecting and concluding data from previous studies. The search for previous research articles was carried out on the Scopus, Science Direct, Clinical Key, SpringerLink, BMC and Google Schoolar portals with keywords in the form is foodstuffs, antioxidants, and infertility which found 8,745 articles. Total of 75 articles met the inclusion-exclusion criteria for used in writing this article. The research was conducted in 2022. Most antioxidants take a role in determining male fertility, such as glutathione, selenium, carotenoids (beta-cryptoxanthin, lycopene, beta-carotene and lutein), zinc, vitamin C, vitamin E, and flavonoids. NAM (Nicotinamide) and carvacrol play a role in determining female fertility. These antioxidants can be found in fruits, vegetables, protein sources and several other plants. Consumption of antioxidant sources is highly recommended to increase fertility, especially for infertile couples.